Benson Relaxation Therapy: Impact on Blood Pressure in Hypertensive Older Adults – A Literature Review - Sani, Ari Wina; Suyasa, I Gede Putu Darma; Nuryanto, I Kadek; Astawa, I Gede Satria (Babali Publisher, 2024)
Introduction: The high incidence of hypertension can have an impact on increasing death rates in the world because it can cause heart failure and coronary heart disease and increase the risk of stroke. A strong emphasis on managing essential HTN with non-pharmacological interventions involving multiple elements of lifestyle modification, focusing on more permanent measures to help improve the overall quality of life and decrease physician dependence and hospitalizations of severe complications. This study aimed to explore the effect of Benson relaxation therapy on blood pressure in older adults with hypertension. Method: The method used in this literature review was to examine the results of previous research in published articles. Article searches were carried out via PubMed, Science Direct, and Google Scholar using the keywords